The Astral traveler's daughter : a school for psychics novel - Archer, K. C. (School for psychics, 2019)
"Last year, Teddy Cannon discovered she was psychic. This year, her skills will be put to the test as she investigates a secretive case that will take her far from home--and deep into the past in the thrilling follow-up to School for Psychics"--